2012
DOI: 10.2166/nh.2012.060b
|View full text |Cite
|
Sign up to set email alerts
|

Improving surface-based precipitation phase determination through air mass boundary identification

Abstract: Most hydrological models apply one empirical formula based on surface air temperature for precipitation phase determination. This approach is flawed as surface precipitation phase results from energy exchanges between falling precipitation and air in the lower atmosphere. Different lower atmospheric conditions cause different precipitation phase probabilities for near-freezing temperatures. Often directly measured lower atmospheric conditions are not available for remote areas. However, meteorological observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Feiccabrino et al [48] found TS and TR values for a group of cold air mass boundaries to be 1 °C warmer than that of all other observations. When these observation groups were analyzed separately, total misclassified precipitation was reduced by 23% in the temperature range −1 to 5 °C.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…Feiccabrino et al [48] found TS and TR values for a group of cold air mass boundaries to be 1 °C warmer than that of all other observations. When these observation groups were analyzed separately, total misclassified precipitation was reduced by 23% in the temperature range −1 to 5 °C.…”
Section: Resultsmentioning
confidence: 84%
“…This was most likely caused by many precipitation events occurring on a sub-daily timescale (most common exception warm frontal light stratiform precipitation) which often ranges from tens of minutes (intense cumuliform precipitation) to several hours in duration [48]. Since temperatures change diurnally with a maximum temperature in the afternoon and a minimum temperature in the morning, a decrease in the temperature sampling time step closer to the time scale to which precipitation events occur would result in a more representative temperature for precipitation phase determination.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations